Atributos químicos e microbiológicos do solo em sistemas agroflorestais do Norte de Minas Gerais - Juliana Martins Ribeiro (2014)
Currently the use of Agroforestry Systems (AFS) has been stimulated as an alternative of more sustainable production, biodiversity conservation and recovery of degraded areas. The present study aimed to evaluate the soil microbiological attributes under three AFS and their respective areas of native vegetation (NV) in two seasons - dry and rainy. The AFS and NV were grouped into two groups according to the soil classification: Udox (AFS1, AFS2 and NV1) and Aqualfl (AFS3 and NV2). In each AFS and NV three composite soil samples were collected, in the layer of 0-5 cm depth for the determination of chemical and granulometric analyzes, total organic carbon (TOC), total nitrogen (TN), Carbon of the Soil Microbial Biomass (SMB-C), basal respiration (BR), metabolic quotient (qCO2) and microbial quotient (qMIC). The soil bulk density of the layer of 0-20 cm depth was obtained by averaging samples collected in the layers of 0-5, 5-10, 10-15 and 15-20 cm depth. The soil fertility evaluation was performed by sampling of the 0-5 and 0-20 cm soil depth. In each assessment time was determined the soil CO2 efflux by a portable infrared gas analyzer (IRGA). For each variable was calculated the average and confidence interval for the test at 5% of probability. The soil fertility of the AFS was similar to VN and the highest nutrient contents were found in the layer of 0-5 cm depth. The management attributed to the systems is contributing to the maintenance of soil density, since the values were similar at all evaluated depths. There were no significant differences in the concentrations and stocks of carbon (C) and nitrogen (N) in the evaluated systems, which confirm that the management adopted in the AFS has contributed to the stability and increase of the stocks of C and N. The SMB-C and BR were higher in the dry season while the CO2 efflux and qCO2 were higher in the wet season. The similar values of the microbiological attributes among the evaluated systems indicate that AFS are keeping the soil biological activity similarly the areas of native vegetation.